1992
DOI: 10.1128/jcm.30.7.1778-1782.1992
|View full text |Cite
|
Sign up to set email alerts
|

Secondary immune response in a vaccinated population during a large measles epidemic

Abstract: The rates of secondary immune response (SIR) and secondary vaccine failure (SYF) during a measles epidemic (10,184 notifications) were evaluated. A patient with SIR was defined as a subject for whom all sera were immunoglobulin G (IgG) positive and IgM negative with a significant increase in complement fixation titer. A patient with SVF was defined as a vaccinated symptomatic subject showing a SIR. Sequential sera from 898 subjects were tested for measles antibody by enzyme-linked immunosorbent assay (IgG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
2
5
0
Order By: Relevance
“…Seronegative people generally develop clinical measles. While seropositivity normally protects against disease, this study confirms that a SIR occurs in at least some protected individuals [12]. Among 44 fully protected, measles late convalescent parents reexposed to measles, four developed an asymptomatic SIR with a significant increase in MV-specific IgG.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Seronegative people generally develop clinical measles. While seropositivity normally protects against disease, this study confirms that a SIR occurs in at least some protected individuals [12]. Among 44 fully protected, measles late convalescent parents reexposed to measles, four developed an asymptomatic SIR with a significant increase in MV-specific IgG.…”
Section: Discussionsupporting
confidence: 68%
“…In this context, the transient nature of the SIR seems to indicate that such individuals can be efficiently protected from disease, but not from infection. The frequency of SIR during measles outbreak was about 5% [12,20], but the number of susceptibles to SIR may be considerably higher. Our data can be used to estimate the frequency of susceptibles on the basis of their pre-existing IgG, NT and HI levels.…”
Section: Discussionmentioning
confidence: 93%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…Symptomatic secondary immune response is mainly seen as secondary vaccine failure and is only rarely found in measles convalescents [Aaby et al, 1986;Edmonson et al, 1990;Miller et al, 1995]. Most estimates of secondary vaccine failure range from 0 [Gustafson et al, 1987;Anders et al, 1996] to about 5% of either the measles patients or the vaccinees [Edmonson et al, 1990;Ozanne and d'Halewyn, 1992]. Measurements of Values are given as exponentials and correspond to the data of Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of seronegative individuals, several observations indicate that measles virus (MV) can circulate also among seropositive persons without signs of clinical measles [Pedersen et al, 1989]. After reexposure to measles, specific IgGpositive subjects may sometimes present with mild disease [Aaby et al, 1986;Edmonson et al, 1990] and protected individuals can develop asymtomatic secondary immune responses [Gustafson et al, 1987;Pedersen et al, 1989;Ozanne and d'Halewyn, 1992]. Subclinical secondary immune response to measles has been observed in immunized populations [Gustafson et al, 1987;Pedersen et al, 1989;Ozanne and d'Halewyn, 1992].…”
Section: Introductionmentioning
confidence: 99%